2011
DOI: 10.1093/nar/gkr675
|View full text |Cite
|
Sign up to set email alerts
|

A second base pair interaction between U3 small nucleolar RNA and the 5′-ETS region is required for early cleavage of the yeast pre-ribosomal RNA

Abstract: In eukaryotes, U3 snoRNA is essential for pre-rRNA maturation. Its 5′-domain was found to form base pair interactions with the 18S and 5′-ETS parts of the pre-rRNA. In Xenopus laevis, two segments of U3 snoRNA form base-pair interactions with the 5′-ETS region and only one of them is essential to the maturation process. In Saccharomyces cerevisiae, two similar U3 snoRNA–5′ ETS interactions are possible; but, the functional importance of only one of them had been tested. Surprisingly, this interaction, which co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(41 citation statements)
references
References 59 publications
2
39
0
Order By: Relevance
“…As one of the core components in the small subunit processome, U3 snoRNP has been shown to have a conserved function in 18S rRNA biogenesis (8,17,23). Depletion of U3 snoRNA in yeast has been shown to lead to underaccumulation of mature 18S rRNA (37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As one of the core components in the small subunit processome, U3 snoRNP has been shown to have a conserved function in 18S rRNA biogenesis (8,17,23). Depletion of U3 snoRNA in yeast has been shown to lead to underaccumulation of mature 18S rRNA (37).…”
Section: Discussionmentioning
confidence: 99%
“…The U3 C/D box snoRNP shown to be universally conserved across eukaryotes is the core component of the small subunit processome essential for 18S rRNA processing (16,17). In plants, it has been reported that the U3 snoRNP forms a stable complex with nucleolin protein 1 (NUC1), which binds nascent pre-RNA at the 5′ ETS and specifically cleaves pre-rRNA at the P site (18)(19)(20).…”
Section: Panmentioning
confidence: 99%
“…The separating cleavage at A 2 as well as the other detectable cleavages in the pre-18S rRNA at sites A 0 and A 1 are dependent on the presence of the U3 snoRNA (originally referred to as snR17 in yeast) (Hughes and Ares 1991). While the U3 snoRNA belongs to the class of box C/D snoRNPs, it does not carry out rRNA methylation, but instead uses three short stretches of its 59 70 nt to base pair with three different sites in the 59ETS to effect prerRNA cleavage Tollervey 1992, 1995;Beltrame et al 1994;Hughes 1996;Mereau et al 1997;Sharma and Tollervey 1999;Borovjagin and Gerbi 2005;Dutca et al 2011;Marmier-Gourrier et al 2011). In general, the presence of the U3 snoRNA has been shown to be required for correct folding of the pre-rRNA (Dutca et al 2011).…”
Section: Nucleolar Pre-rrna Cleavage Steps In Pre-40s Biogenesismentioning
confidence: 99%
“…The 5 ′ ETS is a noncoding region preceding the 18S and contains two essential binding sites, termed A and B here, for U3 snoRNA (Beltrame and Tollervey 1995;Dutca et al 2011;Marmier-Gourrier et al 2011). U3 also binds at two additional sites, called C and D here, in the 5 ′ end and the central region of 18S.…”
Section: Assembly Of the 5 ′ Etsmentioning
confidence: 99%